2017
DOI: 10.1016/j.algal.2017.04.028
|View full text |Cite
|
Sign up to set email alerts
|

Large scale cultivation of genetically modified microalgae: A new era for environmental risk assessment

Abstract: 15The genetic modification of microalgal strains for enhanced or modified metabolic activity 16 shows great promise for biotechnological exploitation. However, of key concern for many is the 17 safety of genetic modification technology and genetically modified organisms with regard to 18 both the environment and human health, and how these concerns are met will play a key role in 19 ensuring how successful commercialisation of genetically modified (GM) algae is achieved. 20Commercialisation opportunities fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
42
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 109 publications
(42 citation statements)
references
References 65 publications
(1 reference statement)
0
42
0
Order By: Relevance
“…The only drawback about microorganisms that have passed through metabolic engineering technology is the probability of some impact on the environment and human health in the case of their release and reproduction in natural habitats. Something like this should be checked by specific committees before their widespread use and commercialization [257].…”
Section: Application Of Metabolic Engineering Technologies To Improvementioning
confidence: 99%
“…The only drawback about microorganisms that have passed through metabolic engineering technology is the probability of some impact on the environment and human health in the case of their release and reproduction in natural habitats. Something like this should be checked by specific committees before their widespread use and commercialization [257].…”
Section: Application Of Metabolic Engineering Technologies To Improvementioning
confidence: 99%
“…Sandoval-Vargas et al (2019) have also recently reported the use of ptxD as a selectable marker for the C. reinhardtii chloroplast, and our combined work adds a useful dominant marker to the molecular toolbox (Esland et al 2018). Importantly, this marker is not derived from a bacterial antibiotic resistance gene and therefore raises less concerns regarding GM regulation (EFSA GMO Panel 2004;Beacham et al 2017). Finally, selection of transformants based on phosphite metabolism does not suffer from false-positive issues as spontaneous mutants able to oxidise phosphite are very unlikely to arise.…”
Section: Discussionmentioning
confidence: 89%
“…Such a metabolic marker is superior to the frequently used antibiotic resistance markers since selection uses a cheap substrate (Phi) and eliminates the problem of 'false positives' since the spontaneous acquisition of Phi metabolism is not possible. Furthermore, the use of metabolic markers helps address the regulatory and safety concerns associated with the environmental spread of antibiotic resistance genes by horizontal gene transfer (HGT) during commercial cultivation (EFSA GMO Panel 2004;Beacham et al 2017). Various reports have shown that ptxD can serve as an efficient marker for generation of transgenic plants (López-Arredondo and Herrera-Estrella 2013; Nahampun et al 2016;Pandeya et al 2017), yeasts (Kanda et al 2014) and cyanobacteria (Selão et al 2019).…”
Section: Introductionmentioning
confidence: 99%
“…However, genetic manipulations and the construction of genetically modified microalgal species containing foreign genes or markers might also raise the safety concerns when considering microalgae as a dietary supplement and a source of high-value nutrients/nutraceuticals. The ecological monitoring and research on the environment and human health impacts of genetically modified microalgae that may persist in and alter natural ecosystems are needed [17,18]. Thus, a safe non-vector approach based on colchicine and cytochalasin B co-treatment to increase DNA levels and total lipid content in Planktochlorella nurekis has been proposed (this study).…”
Section: Total Lipid Content and Fatty Acid Profilementioning
confidence: 99%
“…As nitrogen depletion-mediated increase in lipid content may be accompanied by reduced growth rate and lipid productivity [16], genetic engineering is also considered to overcome such limitations [7,12]. However, genetic manipulations involve the use of foreign genetic material and construction of genetically modified organisms (GMO) that may raise safety concerns and also require additional regulations in terms of the introduction of GMO microalgae into global food market [17,18].…”
Section: Introductionmentioning
confidence: 99%